Effect of Selected Pranayama Practice on Pulmonary Function Tests In Adult Volunteers: A Prospective Interventional Study - Dr. K.Venkatesh; Dr R. Aravind Kumar; Dr. S. Selvakumar; Dr A. Elavarasi (Revista Electronica de Veterinaria, 2024)
Background: Pranayama is an ancient breathing technique that originates from yogic practices in India. It’s a panacea to the modern stress world. Pranayama is the art of controlling the life force of breath. It rejuvenates the body, achieved through the art of breathing which controls our breath with different styles and lengths and has a direct bearing on the basal metabolic rate and the span of longevity. Pranayama is acknowledged to improve lung function and cardiac health. Objectives: The present study evaluates the effect of 10 days and 30 days of pranayama practice on pulmonary functions in adult volunteers.Methods: 40 healthy male volunteers of the age group between 18 – 30 were included in this study. The participants practiced pranayama like pranava, nadisuddhi,kapalabhati, bhastrika, and savitri pranayama,1 hour daily, for 6 days per week, for a total of 30 days of duration. Pulmonary function tests were recorded before the practice of pranayama and after 10 days of practice and followed after 30 days of pranayama practice for the same group of individuals.Results: Pulmonary function parameters were gradually increased after 10 days of practice and 30 days of practice. Among the pulmonary parameters, the Forced vital capacity (FVC), Forced Expiratory Volume in 1st second (FEV1), and Maximum ventilation volume (MVV) and also the FEVI/FVC% were found to be statistically significant (P<0.0001).Conclusion: In this study, the adult volunteers practiced selected pranayama techniques. The practice of pranayama increased the pulmonary function parameters like FVC, FEV1, FEV1/FVC, and MVV for a minimum period of 10 days to 30 days. Hence pranayama may be adopted as the best lifestyle modification to prevent lung diseases and to improve lung function.